STUDY ON THE EFFECT OF PHYSICAL PARAMETER ON THE POWER PRODUCTION OF SOLAR PANEL IN A HYDROPONICS FARM OPTIMIZE ELECTRICITY SUPPLY TO HYDROPONICS FARM - Amrin Laudza'iyy P B, Aflaha
Hydroponics farming use water as growing medium without using any soil. Nutrition is given to the plant by water that go through the growing medium pumped by electric water-pump. This creates a significant demand for electricity in hydroponic farm. To fulfill that demand, solar panel can be used to supply electricity to hydroponic farm. However, solar panel electrical production capacity is easily affected by its surrounding environment thus creating a problem regarding solar panel power production. In this study, solar panel usage in a hydroponic farm in Ciwaruga, West Bandung Regency was studied to determine the electrical production pattern of the solar panel and correlation with the environment where it is installed such as light intensity, panel temperature, air temperature, and air humidity. The result shows that the solar panel power supply share on the total demand of the farm, on average, is only 12.65%. Solar panel power production pattern has correlation with light intensity pattern, however there is inconsistency on the morning where power production doesn’t increase when light intensity increase. Machine learning algorithm using random forest is used to create prediction model of solar power production using environment parameter. The result shows that parameters with significant impact are light intensity with a score of 85.13% and solar altitude angle with a score of 10.94%. The study concluded that power production can be improved by increasing the placement height of the solar panel, using automatic switch to turn on and off the water pump, and using solar tracker to improve solar panel power production.